Mothers' Participation In Community Groups, The Quality Of Prenatal Care Services, And Infant Health: Econometric Analysis (Preliminary Finding) - Heni Wahyuni, Heni Wahyuni; Ariessanti Suryaningrum, Ariessanti Suryaningrum (Fakultas Ekonomika dan Bisnis UGM, 2016)
Underlying theory explains that the production of health is a function of choices, such as those related to individual behavior, nutrition, physical activities, and the utilization of medical care. Mothers' participation in community groups is one possible pathway to increasing the utilization of medical care through access to health-related information, and influencing choices and the production of individual health. Kawachi and Berkman (2000) suggest that the mechanism linking participation and health is the promotion of health information. They argue that in more cohesive communities (more trust or beliefs) health information is rapidly diffused and may influence health seeking behavior. Where there are barriers to access health information through government channels and individual education, as commonly happens in the developing world,The results demonstrate that mothers' participation in arisan has a significant impact on the utilization of prenatal care services and birth weight. These results may suggest that trust and sharing of health knowledge in Indonesia, from participation in arisan, is important for increasing the utilization of prenatal care services and birth weight. Therefore, arisan can be a channel for government to disseminate health related information that may improve mothers' utilization in prenatal care and in turn improve infant health.individual involvement in a community group may provide the resources necessary to seek health information on medical care and to understand health practitioner's advice.